I Gusti Anglurah Panji Sakti: Sebuah Interpretasi dalam Musik Jazz - Ade Surya Firdaus; Hendra Santosa; Ni Wayan Ardini (Universitas Negeri Medan, 2019)
Interpretation of I Gusti Anglurah Panji Sakti is a title of musical composition that interprets or reinterprets the figure of King Panji Sakti who has smart characters, courageous, sympathetic, accommodating, and always close to his subordinates and thick with the Patriotism nature of anti-hegemony, anti-imperialism and anti monopoly in a jazz composition. In the process of its creation, it was motivated by an interest in the figure of Panji Sakti as a King who deserved to be a role model, because of his nationalist and patriotic character which according to the composer was very good in build character of the nation, evident from his living history in speech stories and folklore, through this work the composer also hopes to contribute in reviving the Panji Sakti figure to theother people. This article aims to provide an overview of the process of transforming the figure of King Panji Sakti into jazz music. The process of transformation into jazz music is done by the method of creation from exploration which begins with the study of literature on the history of Panji Sakti and research.in the improvisation step, the composer imagine to find suitable motives to implementing the figure of Panji Sakti and design it so that it becomes the main melodies in this work, then rests on Pono Banoe's opinion about the elements of music namely melody, rhythm and harmony the creator explored the main melody with chords and rhythm which was deemed suitable for this work so that it became a complete musical composition, after which this work was copied into musical notes, and the result is music compositions with a tempo of 100 and beats 4/4, 5 / 4, and 7/4 with key centers G / 1 # (one sharp) and song forms AI, AII, B, and AIII, at the forming step the composer determines the instrument, and chooses supporting musicians who will help in the process of this music.